Peningkatan Efektivitas Pembangunan Desa Melalui Penyederhanaan Penyaluran Dana Desa - Pandu Ario Bismo; Riyo Eka Sahputra (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2021)
The issuance of the Law no. 8 year 2014 on Village had grown an optimism in accelerating village development in Indonesia. However, technical issues such as the late disbursement from the local government, disbursement phases that limit the flexibility in managing the funds, and village governments’ human resource limitations to fulfill the administrative tasks have hampered the effectivity of village funds utilization. Therefore, the Authors try to analyze the existing issues and explore the solutions by using normative legal research method based on regulation, data, theories, and research on the implementation of village funds. As the results, the options such as direct disbursement from the central government to village account and applying two-phase disbursement mechanism of independent villages to all villages should be considered to overcome the aforementioned technical issues.